Geological construction of southern part of Ionian zone based on interpretation of seismic data - BARE, V.; BAKO, P.; NGRESl, V.; BARE, V.; NGRESl, L.; BAKO, M. (Bulletin of the Geological Society of Greece, 2001)
The Ionian zone is the main object of seismic interpretation for a long time. Within this framework, we shall analyze the new seismic intrpretation methods used in oil and gas exploration in the western part of Ionian zone. The Ionian zone is very complex involving certain tectonic faults. In the central part, we can see the duplex tectonic style. Anticline belts from east to west can be interpreted.The Ionian zone comprises three anticline belts:Berati belt, Kurveleshi belt and Cika belt. By application of SeisWork2D in the eastern part of the belt, we have evidenced some perscpective structures, meanwhile in the western part, the seismic quality is very chaotic. Kurveleshi belt is constructed by structures of various forms and dimensions associated with developed tectonics up to thrusting. Cika anticline belt is constructed mainly by prolonged structures of considerable dimensions associated with evaporate outcrops as in Xara, Fterra, Cika etc.